A new UV-spectrophotometric method for the determination of Ornidazole in bulk and in formulations using sodium citrate as hydrotropic solubilizing agent - K.Rajeswar Dutt; Rabha Hani; G.Yeshwanth; V.Bharani; Rayees Ahmed; G. Koteswar Rao; I.Santhosh; K.N.V. Rao. (International Journal of Pharmacy and Analytical Research, 2022)
A thorough literature survey of the various analytical methods for the quantitative estimation of Ornidazole in both bulk drug and dosage forms has revealed that very few analytical methods are available utilizing the hydrotropic solubilisation technique to date. The present research paper is a description n of a new analytical method developed using the principle of Hydrotropy employing very easily available chemical namely 0.75M Sodium citrate solution. The method has been validated as per ICH guidelines and found to conform to ICH guidelines. In the present investigation the use of organic solvent has been avoided due to their high cost, volatility and toxicity, making the method environmental friendly. The findings revealed that the method is new, simple, safe, environmental friendly, accurate, precise, rep roducible and cost-effective. It can be successfully employed as a routine analytical procedure for the analysis of Ornidazole tablets. Hence the authors suggest that this analytical method can be adopted in the Pharmaceutical industry for the analysis of Ornidazole in bulk and various dosage forms. Ornidazole shows its maximum absorbance at 303 nm and Beer’s law was obeyed in concentration range of 1 -5µg/ml in presence of 0.75M Sodium citrate and Molar absorptivity. The statistical analytical parameters namely Correlation coefficient were computed and found to be, 0.950